Ignite-Sparking Youth to Create Healthy Communities: A Protocol for a Community-Centered Effort for the Prevention of Adolescent Obesity - Kidd, Tandalayo; Lindshield, Erika; Kattelmann, Kendra; Adhikari, Koushik; Muturi, Nancy W.; Zies, Susan (My University, 2016)
Objective: To observe outcomes of a community-centered approach to identifying behavioral and environmental factors that influence overweight and obesity in 6th-8th grade youth in selected lowincome, racial/ethnic communities. Design: Five-year, tri-state, quasi-experimental design with environmental assessments and a questionnaire measuring nutrition and physical activity knowledge and behavior conducted in all communities at pre and post. Setting: Low-income, minority communities targeting 6th-8th grade youth. Participants: One experimental and one control communities will be selected via each state’s Cooperative Extension network through an application and review process with the random selection of participating communities. Intervention(s): Academic institutions will work with community leaders to establish and help support community committees tasked to plan, implement and evaluate one nutrition and one physical activity intervention. Main Outcome Measure(s): Assess environmental changes associated with increased intake and variety of fruits and vegetables; decreased intake of foods high in solid fats and added sugars; and an increase in physical activity among 6th-8th grade youth. Analysis: Baseline and post environmental data and pre and post questionnaire data will be analyzed using t-tests, chi-square, and ANOVA with a p < 0.05 to establish statistical significance.